PERAN PEKERJA SOSIAL DALAM PENDAMPINGAN PSIKOSOSIAL ANAK KORBAN KEKERASAN SEKSUAL DI LEMBAGA KONSULTASI KESEJAHTERAAN KELUARGA (LK3) “MELATI” KABUPATEN KARAWANG - Kartika Al Ashzim Kartika Al Ashzim (Social Welfare Study Program, 2018)
Abstract Children are the forerunner of the birth of the next generation that will determine the fate of the nation. Today many children do not get what they are entitled to. That way, the frequent occurrence of violence against children that occurs both in schools, homes, and in public places is more attention to protect children from acts of violence, both physical, psychological and sexual violence. This is the background to understanding the role of social workers in mentoring children victims of sexual violence in LK3